Analisis Strategi Promosi Obyek Wisata Air Putri Waiyoho Kabupaten Seram Bagian Barat - Sandra Dewi; Harold Hursepuny; August J. R. Ufie (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2024)
This study aims to analyze the social media promotion strategy as a promotional medium for the tourist attraction of Air Putri Waiyoho, West Seram Regency. The type of research used is qualitative in the form of descriptive and cannot be measured by numbers. The data sources in this study are primary data and secondary data. Data collection was carried out through observation and interviews. Qualitative data analysis of the Miles and Hubermen model has 3 (three) stages, namely data reduction, data presentation stage, and conclusion drawing and verification stage. The results of data analysis show that the Air Putri tourist attraction has not been promoted online. Online promotion is carried out using Facebook Page, Instagram for Business, and Google My Business. Until now there have been 17 contents posted on FB and IG social media accounts. Promotions using Google My Business are still hampered because the account is temporarily verified by Google. The verification completion process is unknown.  Until now, 32 contents has been available that is ready to be posted until the end of 2023 according to the schedule that has been made. Posts on Instagram for Business get more likes than posts on FB Pages